Role of Knowledge, Subjective Norms, Perceived Behavior Control, and Attitudes in Predict Pro-Environmental Behavior - Muhammad Tamar; Arfah, Triani; Halim, Indri Alviolita; Puspa Akhlakul Karimah (Green Medical Journal, 2021)
Background: One of the public universities as the green campus that prioritizes reforestation to overcome environmental issues. All stakeholders including students are expected to behave pro-environmentally. This study aimed to explain whether or not there is an influence of knowledge, subjective norm, perceived behavior control, and attitude towards pro-environmental behavior (plastic waste) for university students. Methods: This research was conducted under a quantitative approach with 5 valid and reliable variables. In addition, regression tests and structural equation models are used. The respondents of this study were 399 university students from all faculties of Hasanuddin University. Results: Perceived Behavior Control has the greatest effect on pro-environmental behavior compared to other variables. However, environmental knowledge has the smallest effect on subjective norms, perceived behavior control, and attitude. Conclusion: All variables affect predict pro-environmental behavior.